2019
DOI: 10.1016/j.jpainsymman.2019.02.029
|View full text |Cite
|
Sign up to set email alerts
|

A Fixed Nitrous Oxide and Oxygen Mixture for Analgesia in Children With Leukemia With Lumbar Puncture–induced Pain: A Randomized, Double-blind Controlled Trial

Abstract: Context. Leukemia is the most common cancer in the childhood population. Lumbar puncture (LP) plays central role in the diagnosis and treatment process, but options for analgesia are limited.Objectives. The present study aims to evaluate the efficacy of a fixed N 2 O/O 2 mixture to reduce pain in children with leukemia during LP as compared with placebo.Methods. A double-blind, placebo-controlled, and randomized clinical trial involving children who needed LP for diagnosis or treatment was conducted in the ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 37 publications
(32 reference statements)
0
15
0
Order By: Relevance
“…Its analgesic effects have been known for nearly two centuries. Studies (Li et al, 2013; Liu, Gao, Dai, Li, et al, 2018; Liu et al, 2019) have confirmed the safety and efficacy of pre‐mixed nitrous oxide for treatment of cancer patients with breakthrough pain, leukaemia children with pain induced by lumbar puncture, adults with burn wound dressing. The main advantage of the analgesic gas is that it cannot cause loss of consciousness and patients can control gas flow on their own (Maslekar, 2009).…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…Its analgesic effects have been known for nearly two centuries. Studies (Li et al, 2013; Liu, Gao, Dai, Li, et al, 2018; Liu et al, 2019) have confirmed the safety and efficacy of pre‐mixed nitrous oxide for treatment of cancer patients with breakthrough pain, leukaemia children with pain induced by lumbar puncture, adults with burn wound dressing. The main advantage of the analgesic gas is that it cannot cause loss of consciousness and patients can control gas flow on their own (Maslekar, 2009).…”
Section: Introductionmentioning
confidence: 91%
“…Those who agreed to engage in this study and signed the form will be randomly allocated into two groups (intervention and control group). Patients in both groups will receive inhale pre‐mixed nitrous oxide/oxygen or medical air treatment with a one‐way valve, specially designed oral–nasal mask (Qiang et al, 2019). These patients hold the self‐administered mask that can be controlled by their negative pressure to inhale the gas during the dressing change.…”
Section: The Studymentioning
confidence: 99%
See 3 more Smart Citations